Melittin as a Permeability Enhancer II: In Vitro Investigations in Human Mucus Secreting Intestinal Monolayers and Rat Colonic Mucosae - Maher, Sam; Feighery, Linda; Brayden, David J.; McClean, Siobhán (Pharmaceutical research, 2007)
Melittin has shown potential as a non-cytotoxic absorption enhancer in Caco-2 monolayers. Our objectives were to assess in vitro efficacy and cytotoxicity of melittin in two intestinal permeability models and investigate the potential mechanism by which melittin might enhance gastrointestinal absorption. The effects of melittin were examined in the mucus-secreting intestinal cell monolayers, HT29-MTX-E12 (E12), using transepithelial electrical resistance (TER), transmission electron microscopy (TEM) and the MTT viability assay. The effects of melittin on TER, permeability and short circuit current (Isc) were also investigated in rat colon mucosae mounted in Ussing chambers. Ion transporting capacity of tissue was measured in response to secretagogues as surrogate markers of cytotoxicity. Melittin stability was examined by a means of a hemolytic assay. The mechanism by which melittin decreases TER across the rat mucosa was examined with a range of enzymatic inhibitors. Apical addition of melittin resulted in a reversible non-cytotoxic concentration-dependent decrease in TER across E12 monolayers, which was independent of the presence of mucus. Apical addition of melittin reduced TER and increased the permeability of [(14)C]-mannitol across rat colonic mucosae. The melittin-induced drop in TER in rat colon was significantly attenuated by W7 suggesting partial mediation by calmodulin. The rapid and reversible nature of melittin's permeation enhancing properties and its limited cytotoxicity in polarized intestinal epithelia, suggests a potential drug delivery role for the peptide in oral formulations of poorly absorbed drugs.